2020
DOI: 10.1101/2020.10.13.20211813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precautionary breaks: planned, limited duration circuit breaks to control the prevalence of COVID-19

Abstract: The COVID-19 pandemic in the UK has been characterised by periods of exponential growth and decline, as different non-pharmaceutical interventions (NPIs) are brought into play. During the early uncontrolled phase of the outbreak (early March 2020) there was a period of prolonged exponential growth with epidemiological observations such as hospitalisation doubling every 3-4 days (growth rate r≈0.2). The enforcement of strict lockdown measures led to a noticeable decline in all epid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“… 15 Another study looking at short-term, so-called circuit breaker interventions in the UK found that such interventions have the biggest impact when the growth rate is low. 16 The authors concluded that such interventions are not long-term solutions but can buy time to improve other control measures, such as testing, contact tracing and isolation, or introduction of a vaccine.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Another study looking at short-term, so-called circuit breaker interventions in the UK found that such interventions have the biggest impact when the growth rate is low. 16 The authors concluded that such interventions are not long-term solutions but can buy time to improve other control measures, such as testing, contact tracing and isolation, or introduction of a vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…We show that a lockdown is either effective within a few weeks, or tends to fail its aim. If effective, recurring lockdowns are not necessary — contrary to the oscillating dynamics previously presented in the context of circuit breakers 4;5;6 , and contrary to a regime with high case numbers — if moderate contact reductions are maintained. Hence, at low case numbers, the control is easier, and more freedom can be granted.…”
mentioning
confidence: 88%
“…Once the number of new infections has overwhelmed the TTI system, re-establishing control can be challenging. A recent suggestion is the application of a circuit breaker 4;5;6 , a short lockdown to significantly lower the number of daily new infections. Already during the first wave, lockdowns have proven capable to lower case numbers by a factor 2 or more every week (corresponding to an observed reproduction number of .…”
Section: Analytical Framework: Overviewmentioning
confidence: 99%
“…We adapt an existing age and regionally structured model of SARS-COV-2 dynamics that has been matched to UK data [12,13] to include the consequences of vaccination [11]. The model captures the historic trends of infection, hospitalisation and deaths in the UK, including the scale of the first and second waves.…”
Section: The Mathematical Model and Vaccination Assumptionsmentioning
confidence: 99%